Orthotopic equine study confirms the pivotal importance of structural reinforcement over the pre‐culture of cartilage implants - Mylène deRuijter; Paweena Diloksumpan; Inge Dokter; Harold Brommer; Ineke H. Smit; Riccardo Levato; P. René vanWeeren; Miguel Castilho; Jos Malda (Wiley, 2024)
Abstract In articular cartilage (AC), the collagen arcades provide the tissue with its extraordinary mechanical properties. As these structures cannot be restored once damaged, functional restoration of AC defects remains a major challenge. We report that the use of a converged bioprinted, osteochondral implant, based on a gelatin methacryloyl cartilage phase, reinforced with precisely patterned melt electrowritten polycaprolactone micrometer‐scale fibers in a zonal fashion, inspired by native collagen architecture, can provide long‐term mechanically stable neo‐tissue in an orthotopic large animal model. The design of this novel implant was achieved via state‐of‐the‐art converging of extrusion‐based ceramic printing, melt electrowriting, and extrusion‐based bioprinting. Interestingly, the cell‐free implants, used as a control in this study, showed abundant cell ingrowth and similar favorable results as the cell‐containing implants. Our findings underscore the hypothesis that mechanical stability is more determining for the successful survival of the implant than the presence of cells and pre‐cultured extracellular matrix. This observation is of great translational importance and highlights the aptness of advanced 3D (bio)fabrication technologies for functional tissue restoration in the harsh articular joint mechanical environment.